2018
DOI: 10.3389/fphys.2018.00598
|View full text |Cite
|
Sign up to set email alerts
|

Protein and the Adaptive Response With Endurance Training: Wishful Thinking or a Competitive Edge?

Abstract: The significance of carbohydrates for endurance training has been well established, whereas the role of protein and the adaptive response with endurance training is unclear. Therefore, the aim of this perspective is to discuss the current evidence on the role of dietary protein and the adaptive response with endurance training. On a metabolic level, a single bout of endurance training stimulates the oxidation of several amino acids. Although the amount of amino acids as part of total energy expenditure during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…Hence, the international society of sports nutrition recommends endurance athletes to consume a high CHO diet containing 8-12 g of CHO kg − 1 day − 1 to maximize the endogenous glycogen stores and 1.2 g kg − 1 h − 1 following strenuous exercise to replenish the glycogen stores [2]. Additionally, within the last decade attention has been given to protein (PRO), due to its possible role in maximizing the adaptational responses to endurance training [3]. Endurance training is characterized by repetitive, relatively low power output muscle contractions performed over a prolonged period, causing a metabolic and mechanical stress on the muscle [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the international society of sports nutrition recommends endurance athletes to consume a high CHO diet containing 8-12 g of CHO kg − 1 day − 1 to maximize the endogenous glycogen stores and 1.2 g kg − 1 h − 1 following strenuous exercise to replenish the glycogen stores [2]. Additionally, within the last decade attention has been given to protein (PRO), due to its possible role in maximizing the adaptational responses to endurance training [3]. Endurance training is characterized by repetitive, relatively low power output muscle contractions performed over a prolonged period, causing a metabolic and mechanical stress on the muscle [4].…”
Section: Introductionmentioning
confidence: 99%
“…Stress, which may cause myofibrillar disruption, and activation of signaling pathways which enhance myofibrillar and mitochondrial muscle protein synthesis (MPS) [4]. Thus, in order to provide amino acids for skeletal muscle accretion, a protein intake above the recommended level for sedentary or moderately active people (RDA; 0.8 g protein kg − 1 d − 1 ) is suggested to improve recovery [5], but also trainings adaptations [3]. Furthermore, within recent years, a number of studies have demonstrated that high volume endurance exercise increase whole body amino acid oxidation and enhance the need for protein up to 1.8 g of PRO kg − 1 day − 1 [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the international society of sports nutrition recommends endurance athletes to consume a high CHO diet containing 8-12 g of CHO kg -1 day -1 to maximize the endogenous glycogen stores and 1.2 g kg -1 h -1 following strenuous exercise to replenish the glycogen stores (2). Additionally, within the last decade attention has been given to protein (PRO), due to its possible role in maximizing the adaptational responses to endurance training (3). Endurance training is characterized by repetitive, relatively low power output muscle contractions performed over a prolonged period, causing a metabolic and mechanical stress on the muscle (5).…”
Section: Introductionmentioning
confidence: 99%
“…Stress, which may cause myo brillar disruption, and activation of signaling pathways which enhance myo brillar and mitochondrial muscle protein synthesis (MPS) (5). Thus, in order to provide amino acids for skeletal muscle accretion, a protein intake above the recommended level for sedentary or moderately active people (RDA; 0.8 g protein kg -1 d -1 ) is suggested to improve recovery (6), but also trainings adaptations (3). Furthermore, within recent years, a number of studies have demonstrated that high volume endurance exercise increase whole body amino acid oxidation and enhance the need for protein up to 1.8 g of PRO kg -1 day -1 (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Stress, which may cause myo brillar disruption, but also induce activation of signaling pathways which enhance myo brillar and mitochondrial muscle protein synthesis (MPS) and thereby tissue remodeling and mitochondrial biogenesis (5). Thus, in order to provide amino acids for skeletal muscle accretion, a protein intake above the recommended level for sedentary or moderately active people (RDA; 0.8 g protein kg − 1 d − 1 ) is suggested to improve recovery (6), but also trainings adaptations (3). Furthermore, within recent years, a number of studies have demonstrated that high volume endurance exercise increase whole body amino acid oxidation and enhance the need for protein up to 1.8 g of PRO kg − 1 day − 1 (7,8).…”
Section: Introductionmentioning
confidence: 99%